Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

-2(11-12x) = -4(1-6x)

Sagot :

Answer:

0=18

Step-by-step explanation:

not simplified.

Answer:

There is no answer.

Step-by-step explanation:

-2(11 - 12x) = -4(1-6x)

First you need to simplify the equation, using distributive property.

Distribute -2 to the numbers within the parentheses.

-2*11 = -22

-2*-12x =24x

= 24x - 22

Then distribute -4 among 1 and -6.

-4*1 =-4

-4*-6x = +24x

= 24x - 4

And because

24x - 22 does NOT equal 24x - 4

There is no answer because they are not equivalent, making the equation itself false/untrue.

We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.